Artificial Intelligence (AI) Utilization And Student Learning Motivation: A Literature Review In Human Resource Management Perspective In The Digital Economy Era - Andi Nurfiana Haz; Chairunnisaa M Z Huzaen (International Journal of Economics and Development, 2026)
The digital economy era has transformed higher education by increasing the demand for adaptive, technology-oriented, and highly competent human resources. This transformation requires not only technological readiness but also psychological preparedness among students as a future talent pool. This study examines the utilization of Artificial Intelligence (AI) and its relationship with students’ learning motivation from a Human Resource Management (HRM) perspective in the digital economy era. The study employs a qualitative approach using a literature review method, synthesizing findings from seven relevant scholarly articles published between 2025 and 2026. The reviewed literature consistently indicates that the combined influence of AI utilization and learning motivation is positively associated with improvements in students’ academic performance. Several studies highlight that students who effectively utilize AI tools and demonstrate strong learning motivation tend to achieve better academic outcomes, enhanced learning efficiency, and greater readiness for future workforce demands. AI functions as an effective cognitive support tool by personalizing learning materials, enhancing learning efficiency, and fostering creativity. However, the literature also highlights the potential risk of digital dependency when AI adoption is not accompanied by intrinsic motivation to acquire knowledge. Therefore, learning motivation plays a crucial mediating role in maintaining academic integrity and promoting meaningful learning. From a human capital development perspective, higher education institutions serve as the primary source of future talent for organizations operating in the digital economy. Students who demonstrate strong learning motivation and AI proficiency are more likely to adapt quickly and perform effectively in the labor market. The findings suggest that the integration of AI technology with effective motivation management is essential for developing agile, adaptive, and competent human capital. Consequently, universities should promote responsible AI adoption while strengthening students’ intrinsic motivation to support sustainable learning outcomes, workforce readiness, and long-term organizational competitiveness in the era of digital economic transformation.